Analisis Komparatif Tanggung Jawab Fidusia Direksi dan Perlindungan Pemegang Saham Minoritas: Studi Kritis Terhadap Hukum Perseroan di Indonesia dan Singapura - Michael Hagana Bangun (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research compares corporate law in Indonesia and Singapore with regard to the fiduciary duties of directors and the protection of minority shareholders. The study employs a normative legal research method (juridical-normative research). This approach is chosen because the object of analysis focuses on positive legal norms, legal principles, doctrines, and comparisons of the legal systems in Indonesia and Singapore. This study does not examine sociological aspects or societal behavior; instead, it emphasizes dogmatic legal analysis and relevant court decisions. Data were collected through library research by reviewing physical and digital literature using legal databases such as Westlaw, HeinOnline, and the Indonesian Supreme Court decision directory. The collected data were analyzed qualitatively using the deductive syllogism method—drawing specific conclusions from general legal premises—and a comparative interpretation method to construct logical, systematic, and prescriptive legal arguments. The research findings indicate that although Indonesia and Singapore share the same objective of establishing good corporate governance, their legal approaches differ significantly due to their respective legal origins..